PEMANFAATAN AGAR-AGAR SERBUK SEBAGAI PENAMBAH PEKTIN PADA BUAH PEPAYA (Carica papaya L.) UNTUK FORMULASI SELAI LEMBARAN - Ulfa, Dini; Priyono, Suko; Bandem, Putu Dupa (Jurnal Sains Mahasiswa Pertanian, 2015)
ABSTRACT The aims of this research is to get the seaweed formulation as a pectin addition to papaya concentrate for resulting physicochemical and sensory characteristic of the best papaya jam. This research design used is Randomized Block Design (RBD) consisting of one factor threatment is the addtion of the concentration of seaweed powder that consist of nine standards treatment are a1=5 g, a2= 7 g, a3= 9 g, a4=11 g, a5= 13 g, a6= 15 g, a7= 17 g, a8= 19 g dan a9= 21 g. The variables measured were the physicochemical and sensory character. The addition of seaweed powder concentrate has a effect unreal to water content, vitamine C, jam pH and total dissolved solids. Based on the physicochemical and sensory test sheet concentration addition papaya jam jelly powder yields a value of 7 g treatment (NP) the best is 0.636 with a water content of 48.941%, vitamine C 58.667mg/100g, jam pH 3.877, total dissolved solids 49.266% and sensory character that plasticity (a little plasticity), 3.17, plasure 3.14 (like), taste 3.97 (too sweet andÂ  acid), aroma 3.17 (its not papaya aroma) and appearance 2.31 (a little firm). Â  Keywords: powder seaweed, physicochemical, sensory, papaya jam sheet